2022
DOI: 10.1111/ina.13120
|View full text |Cite
|
Sign up to set email alerts
|

A global burden assessment of lung cancer attributed to residential radon exposure during 1990–2019

Abstract: This study aimed to explore the spatial and temporal trends of lung cancer burden attributable to residential radon exposure at the global, regional, and national levels. Based on the Global Burden of Disease Study (GBD) 2019, we collected the age‐standardized mortality rate (ASMR) and age‐standardized disability‐adjusted life rate (ASDR) of lung cancer attributable to residential radon exposure from 1990 to 2019. The Joinpoint model was used to calculate the annual average percentage change (AAPC) to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
(111 reference statements)
0
7
0
Order By: Relevance
“…The results of this study indicated that the burden of LC caused by residential radon exposure in China steadily increased over the past 30 years. According to relevant literature reports, the overall burden of LC worldwide and the burden of LC attributed to residential radon exposure have both decreased over the past three decades (Diseases and Injuries, 2020; Shan et al ., 2022). In 2019, the ASMR and ASDR for LC attributed to residential radon exposure decreased by 15.6% and 23.0%, respectively, globally (Shan et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this study indicated that the burden of LC caused by residential radon exposure in China steadily increased over the past 30 years. According to relevant literature reports, the overall burden of LC worldwide and the burden of LC attributed to residential radon exposure have both decreased over the past three decades (Diseases and Injuries, 2020; Shan et al ., 2022). In 2019, the ASMR and ASDR for LC attributed to residential radon exposure decreased by 15.6% and 23.0%, respectively, globally (Shan et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…According to relevant literature reports, the overall burden of LC worldwide and the burden of LC attributed to residential radon exposure have both decreased over the past three decades (Diseases and Injuries, 2020; Shan et al ., 2022). In 2019, the ASMR and ASDR for LC attributed to residential radon exposure decreased by 15.6% and 23.0%, respectively, globally (Shan et al ., 2022). This is in opposite to the findings of this study regarding the disease burden of LC caused by residential radon exposure in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the validity of our estimates of harm and to contextualize them, we compare them with independent estimates of chronic health impacts (in DALYs) from the inhalation of airborne contaminants in dwellings. Three studies conducted in the United States of America ,, applied the IND-DALY and/or ID-DALY methods, and three global/European studies ,, followed a comparative risk assessment approach using the population attributable fraction. A more detailed comparison can be found in Supporting Figure A.…”
Section: Discussionmentioning
confidence: 99%
“…This change is not solely attributed to our methodology because it is similar to those followed in previous studies of harm in dwell-ings. 8,12,18,19,24,114 Formaldehyde, radon, and ozone have data from both epidemiology and toxicology studies. However, PM 2.5 , PM 10−2.5 , and nitrogen dioxide are characterized only by epidemiological data.…”
Section: Concentrations Of Airborne Contaminants In Dwellingsmentioning
confidence: 99%